Macrofloral diversity of Bulabog-Putian Natural Park, Dingle, Iloilo, Philippines - Elefan, Ernesto S. (Silliman Journal, 2010)
Macrofloral species richness, relative density, relative abundance and diversity index of the protected forest and riverine ecosystems of Bulabog-Putian Natural Park, Dingle, Iloilo, Philippines were determined employing the modified quadrat method. There were 68 families, 170 genera, and 218 plant species listed in the entire study area of 0.16 hectare. The riverine ecosystem had a higher species richness (S=137) compared with the protected forest ecosystem (S=126). The top three major families observed in the protected forest ecosystem were Euphorbiaceae, Moraceae, and Annonaceae families and for the riverine ecosystem they were the Moraceae, Poaceae, Euphorbiaceae and Papilionaceae families. Plant genera that belong to the families Euphorbiaceae and Annonaceae dominated the protected forest ecosystem and the plant genera belonging to families Poaceae and Cyperaceae dominated the riverine ecosystem. Relative abundance in the herb-dominated riverine ecosystem was significantly higher than of the tree-dominated protective forest ecosystem with values of 43,466 and 7,007 individuals, respectively. computed diversity index was higher in the riverine ecosystem (H'=2.69), both categorized as areas of moderate level of species diversity. In the entire study area, 28 (12.84%) plant species are known to have threatened conservation status; three of these are critically endangered, namely kamagong (Diospyros philippensis Desr.) Gurke), prickly narra (Pterocarpus indicus Willd. forma echinatus) and red lauan (Shorea negrosensis Foxw.), Endemic plant species were inventoried that need to be conserved and protected. This study provides comprehensive baseline information on the macrofloral diversity of Bulabog-Putian National Park. Data gathered from this study will enhance knowledge on biodiversity for the local or national government to implement strong conservation and protection programs for the endemic and indigenous plant species in their natural habitat and to prevent biodiversity loss that may be aggravated by climate change.